Civil society, transitions, and Post War Reconstruction in Latin America : a comparison of El Salvador, Guatemala and Perú - koonings, Kees (Estocolmo SE: Institute of Latin American Studies, 2002)
Analiza el papel de la sociedad civil en tres casos recientes de transición política y de reconstrucción post-conflicto: El Salvador, Guatemala y Perú.
Keywords: EL SALVADOR; GUATEMALA; PERU; SOCIEDAD CIVIL; POSTGUERRA